2022
DOI: 10.1021/acs.joc.2c00949
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylate-Assisted Iridium (III)-Catalyzed C(sp2)–H Amidation of 2-Aroylimidazoles With Dioxazolones

Abstract: The Ir(III)-catalyzed ortho C−H amidation of 2aroylimidazoles with 3-aryldioxazolones as an amidating reagent is reported. The method provides a broad substrate scope with wide functional group compatibility. Mechanistic studies indicate that C−H bond cleavage is reversible and appears not to be the ratedetermining step. The presence of an electron-donating group in the 2-aroylimidazoles and an electron-withdrawing group in the 3aryldioxazoles significantly accelerates the reaction, suggesting that nitrene ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 51 publications
0
12
1
Order By: Relevance
“…To gain further insights into the reaction mechanism, kinetic studies using the initial rate method were performed, and it was found that the catalyst [Cp*IrCl 2 ] 2 and TrocN 3 follow first-order kinetics while the 2-benzoylimidazole 1a was a negative first-order (Scheme f). These results suggest that the catalyst and the coupling partner both have a major role in the rate-determining step and that a dormant species appears to be formed from two molecules of 1a which might then participate in an off-catalytic cycle and be in equilibrium with the active catalytic species, as was observed in our previous work . We used variable temperature techniques to determine the activation energy for this model reaction (Scheme g), and the value was found to be 64.38 kJ mol –1 (15.39 kcal mol –1 ).…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…To gain further insights into the reaction mechanism, kinetic studies using the initial rate method were performed, and it was found that the catalyst [Cp*IrCl 2 ] 2 and TrocN 3 follow first-order kinetics while the 2-benzoylimidazole 1a was a negative first-order (Scheme f). These results suggest that the catalyst and the coupling partner both have a major role in the rate-determining step and that a dormant species appears to be formed from two molecules of 1a which might then participate in an off-catalytic cycle and be in equilibrium with the active catalytic species, as was observed in our previous work . We used variable temperature techniques to determine the activation energy for this model reaction (Scheme g), and the value was found to be 64.38 kJ mol –1 (15.39 kcal mol –1 ).…”
Section: Resultsmentioning
confidence: 53%
“…These results suggest that the catalyst and the coupling partner both have a major role in the ratedetermining step and that a dormant species appears to be formed from two molecules of 1a which might then participate in an off-catalytic cycle and be in equilibrium with the active catalytic species, as was observed in our previous work. 8 We used variable temperature techniques 14 to determine the activation energy for this model reaction (Scheme 2g), and the value was found to be 64.38 kJ mol −1 (15.39 kcal mol −1 ).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…α-Amino carbonyls, as a class of N-containing compounds, are not only ubiquitous structural motifs in natural products and pharmaceuticals but also high-value synthons of N-heterocycles and chiral 1,2-amino alcohols. However, the traditional synthesis of α-amino carbonyls often suffers from the requirement of prefunctionalized starting materials or the scarce availability of N-electrophiles. , C–H amidation realized by transition-metal-catalyzed nitrene transfer has several advantages including eliminating the requirement of prefunctionalized starting materials and the formation of undesired byproducts. Transition metals, such as Ir, Rh, Co, , Ru, , Cu, , and Pd, are usually used as catalysts for these nitrene transfer reactions. This advanced synthetic strategy has been gradually employed to the construction of α-amino carbonyls in recent years but still faces the challenge of limiting substrate scope or low functional group compatibility. Noteworthily, Chatani’s group recently reported Ir-catalyzed selective α-amidation to synthesize α-amino carbonyls with a broad range of carbonyl substrates (2-acylimidazoles) .…”
Section: Introductionmentioning
confidence: 99%